2006
DOI: 10.3758/bf03193856
|View full text |Cite
|
Sign up to set email alerts
|

Proverb preferences across cultures: Dialecticality or poeticality?

Abstract: Peng and Nisbett (1999) claimed that members of Asian cultures show a greater preference than Euro-Americans for proverbs expressing paradox (so-called dialectical proverbs; e.g., Too humble is half proud). The present research sought to replicate this claim with the same set of stimuli used in Peng and Nisbett's Experiment 2 and a new set of dialectical and nondialectical proverbs that were screened to be comparably pleasing in phrasing. Whereas the proverbs were rated as more familiar and (in Set 1) more poe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…And when Eastern (Japanese) participants have a direct stake in the contradiction (someone is stating a view point opposite their own), they behave exactly as Westerners (French) participants, favoring their own position (Mercier,Van der Henst,17 The first two experiments dealt with preferences for dialectical or non--dialectical proverbs. The difference that was observed in Peng & Nisbett (1999), however, seems to be the result of a confound, and has proven hard to replicate (Friedman, Chen, & Vaid, 2006). Yama, Kawasaki, & Adachi, submitted; Van der Henst, Mercier, Yama, Kawasaki, & Adachi, 2007).…”
mentioning
confidence: 99%
“…And when Eastern (Japanese) participants have a direct stake in the contradiction (someone is stating a view point opposite their own), they behave exactly as Westerners (French) participants, favoring their own position (Mercier,Van der Henst,17 The first two experiments dealt with preferences for dialectical or non--dialectical proverbs. The difference that was observed in Peng & Nisbett (1999), however, seems to be the result of a confound, and has proven hard to replicate (Friedman, Chen, & Vaid, 2006). Yama, Kawasaki, & Adachi, submitted; Van der Henst, Mercier, Yama, Kawasaki, & Adachi, 2007).…”
mentioning
confidence: 99%
“…In other words, compared to Westerners, Easterners have a stronger tendency to view the world as contradictory and, thus, interpret their thoughts as being composed of positive and negative aspects in their cultural practices. However, Friedman, Chen, andVaid, 2006 (2006) did not replicate Peng and Nisbett's (1999) results using contradictory proverbs. Both Chinese and Americans preferred dialectical proverbs to Running Head: CULTURE AND THINKING 13 non-dialectical ones and judged the dialectical type as wiser.…”
Section: This Distinction Has Been Discussed In Terms Of the Contrastmentioning
confidence: 71%
“…In their study, Friedman, Chen and Vaid (2006) tried to determine whether the finding by Peng and Nisbett (1999, Experiment 2) that Asians prefer dialectical over nondialectical proverbs more than Americans do was replicable. The results of their study indicated that it is not; the failure to replicate Peng and Nisbett's finding was all the more noteworthy given that their dialectical and nondialectical stimulus sets included the same items used in Peng and Nisbett's Experiment.…”
Section: Literature Reviewmentioning
confidence: 96%